PENGGUNAAN METODE TUTOR SEBAYA DALAM MEMBANTU PESERTA DIDIK YANG BERKEMAMPUAN RENDAH PADA TINGKAT SEKOLAH DASAR - Mariana Jediut; Fransiska Jaiman Madu (JIPD (Jurnal Inovasi Pendidikan Dasar), 2021)
Abstract Education is related to learning and the implementation of learning is always related to learning methods. The learning method is an ordinary thing that is always discussed and even some people consider it to be an unimportant issue. This study aims to describe the use of peer tutoring methods in helping elementary school students with low abilities. This research uses literature study method. The data collection is done by tracing various relevant literatures. Data were analyzed using descriptive and comparative methods. The results of the study show that the use of peer tutoring methods can improve the ability of elementary school students. The implementation steps are 1) to recruit students with good abilities; 2) capture low-ability students; 3) the formation of heterogeneous groups; 4) determine the material for each group; 4) tutor guidance; 5) determining the schedule of activities; 6) checking the results of peer tutoring activities; 7) follow-up.